Análise do consumo de bens e serviços artístico-culturais no Brasil metropolitano - Sibelle Cornelio Diniz (2009)
This work aims to evaluate the determinants of the consumption of artistic-cultural goods and services in Brazil, conceiving this consumption as an activity with positive effects on consumer and on society as a whole. We draw on the microeconomic approach of human capital and additional approaches from the institutionalist and sociological perspectives, according to which the present consumption of these kinds of goods is strongly determined by previous exposure. Taking on this premise, we try to identify the individual characteristics that influence this exposure. We estimate a model in which the expenditure on artistic-cultural goods and services depends on socioeconomic, educational and sociodemographic characteristics of the head of the household, and on variables that indicate the location of the household. The data comes from the Household Survey of Familiar Budgets (POF) and the Survey of Municipal Information (MUNIC) from the Brazilian Institute of Geography and Statistics (IBGE). They cover nine metropolitan regions and the Federal District. The results indicate that the artistic-cultural expenditure is highly concentrated and strongly determined by income and education of the consumer. Furthermore, the expenditure differs regionally, what may occur due to supply variations or historic-cultural distinctions. We conclude that the distribution of the expenditure follows from structural inequalities in the Brazilian society, indicating that cultural policies should be guided not only by the expansion of the supply, but also through stimulus on the demand side by the reduction of educational and access disparities. Finally, we stress the importance of the mass media in the feed of cultural demands from the Brazilian society, since this is the source of the cultural goods and services accessed by the majority of the population.